2019
DOI: 10.1093/jcmc/zmz007
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minorities’ Social Media Political Use: How Ingroup Identification, Selective Exposure, and Collective Efficacy Shape Social Media Political Expression

Abstract: Latinos represent a large ethnic minority group in the United States, but their political participation, including on social media, is low compared to other groups. Guided by social identity and social cognitive theories, this study examines the influence of two dimensions of ingroup identification (i.e., group self-definition, group self-investment) on Latinos(as)' political expression about immigration and Latino culture on social media, the mediating role of pro-attitudinal selective exposure to media conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Therefore, this study extends Velasquez and colleagues' (2019) findings by incorporating and interrogating the role of perceived barriers to group permeability and synthesizes findings from Armenta et al (2017) with results from Velasquez et al (2019). If weak barriers to group permeability weaken one's in-group identification (Armenta et al, 2017), and in-group identification is positively associated with social media expression (Velasquez et al, 2019), then perceptions of group status impermeability should also be positively related to social media expression.…”
Section: Group Status (Im)permeability and Social Media Expressionsupporting
confidence: 62%
See 4 more Smart Citations
“…Therefore, this study extends Velasquez and colleagues' (2019) findings by incorporating and interrogating the role of perceived barriers to group permeability and synthesizes findings from Armenta et al (2017) with results from Velasquez et al (2019). If weak barriers to group permeability weaken one's in-group identification (Armenta et al, 2017), and in-group identification is positively associated with social media expression (Velasquez et al, 2019), then perceptions of group status impermeability should also be positively related to social media expression.…”
Section: Group Status (Im)permeability and Social Media Expressionsupporting
confidence: 62%
“…When group boundaries are perceived as permeable, in-group identification becomes weaker (Armenta et al, 2017). Simultaneously, prior evidence (Velasquez et al, 2019) suggests a positive relationship between in-group identification and social media expression. Specifically, Velasquez et al (2019) found that increased group self-definition (including factors such as self-stereotyping and perceived in-group homogeneity) was associated with Latinos' increased social media expression about immigration.…”
Section: Group Status (Im)permeability and Social Media Expressionmentioning
confidence: 97%
See 3 more Smart Citations